The work of management : a leader's guide to applying systems leadership - Macdonald, Ian, 1950 October 23-; Burke, Catherine G., 1939-; Stewart, Karl (Routledge, 2025)
"The Work of Management demonstrates how the concepts, models, and tools of Systems Leadership can be applied, enabling you to become a more effective manager by improving your own work to create a more positive and effective organization. Positive organizations, where people come together to achieve a productive and personally satisfying purpose, and which provide the basis for a good society, do not occur by chance. They are created by the work of leaders and members who are dependent upon the way the organization is designed and operates - its structure and systems. While the theory is explained, this book primarily presents the practical aspects - the specific values, methods and tools - that can be used to improve work and the work performance of direct reports. Building on the bestselling book, Systems Leadership, this book provides leaders with a manual for the application of concepts as well as an introduction to Systems Leadership Theory, a method that has been used successfully by businesses from large multinational firms and banks to SMEs as well as public agencies and NGOs. It provides a predictive capability, allowing a leader to predict what will work well and what is likely to fail, according to the context. It gives the benefit of foresight as decisions must be made. Designed as a leader's manual for the application of the concepts around Systems Leadership, this book is for people who want to improve their own, and their organization's, work practices and performance"-- Provided by publisher.
Keywords: Management.; Organizational sociology.; Organizational effectiveness.; Leadership.; elektronické knihy; electronic books